FAKTOR-FAKTOR PENGHAMBAT ASEAN INTERGOVERNMENTAL COMMISSION ON HUMAN RIGHTS (AICHR) DALAM PENEGAKAN HAK ASASI MANUSIA DI ASIA TENGGARA - Fiari Larasati Putri Irawan; Agus Subagyo; Jusmalia Oktaviani (Universitas Jenderal Ahmad Yani, 2017)
ASEAN Intergovernmental Commission on Human Rights (AICHR)is an inter-governmental organization under the auspices ofASEAN, which focuses on human rights at the regional level.AICHR was established in 2009 and consists of 10representatives from each ASEAN countries. Broadly speakingAICHR has two primary mandates which are function to promoteand to perform protection against human rights.The general objective of this research is to describe AICHR as aregional human rights commission, and the specific objectives ofthis research are to describe and analyze the Inhibiting factors ofAICHR In Enforcement of Human Rights in Southeast Asia.Researcher used qualitative research methods and descriptiveanalysis research type. The technique of collecting primary datawas conducted through some interviews and secondary datacollection techniques by literature study. Researcher applied theapproach of Institutional Neoliberalism, the InternationalOrganization Theory, Regime Theory, and Concept of HumanRights as an analytical tool.In this research it can be concluded that there are four inhibitingfactors of the AICHR in Enforcement of Human Rights inSoutheast Asia, including Principles of ASEAN Way which thereare the principle of non-intervention and state sovereignty;Decision Making based on Consensus; Lack mandate of functionto protection in the ToR of AICHR; and the last, there are PoliticalInterests of Each Countries of ASEAN which includes DifferingViews of Each ASEAN Countries against Human Rights and theirCommitment to Human Rights.